New data on the spider fauna of Iran (Arachnida: Aranei), Part VI - A. Zamani; A.V. Tanasevitch; A.A. Nadolny; S.L. Esyunin; Yu.M. Marusik (KMK Scientific Press Ltd., 2022)
A family (Zoropsidae), five genera (Archaeodictyna Caporiacco, 1928, Microneta Menge, 1869, Sintula Simon, 1884, Zilla C.L. Koch, 1836, Zoropsis Simon, 1878), and 26 spider species are recorded in Iran for the first time. New provincial records for 61 species are presented. Considering the new results, 746 spider species are known from Iran.